A Tensor based Precoder and Receiver for MIMO GFDM systems - Pandey, Divyanshu; Leib, Harry (IEEE International Conference on Communications (2003), 2021)
Generalized Frequency Division Multiplexing (GFDM) is a multi-domain communication scheme where data symbols are transmitted over a time-frequency block. Tensors, which are multi-way arrays, can be efficiently used to model such systems. This paper presents a system model for a multiple input multiple output (MIMO) GFDM system using the Einstein product of tensors. The input and output are modelled as order 3 tensors where the three modes correspond to space, time and frequency domains. The equivalent channel between the input and output obtained from a cascade of transmit filter, physical channel and receive filter, is defined as an order 6 tensor which takes into account interference across all the domains. An information theoretic analysis of such a tensor channel is presented which is then used to develop a tensor based precoding scheme for MIMO GFDM systems. The effect of various GFDM pulse shape parameters on the capacity of the equivalent channel is explored. A multi-linear minimum mean square error (MMSE) receiver using the tensor framework is also presented.